Evaluation of the Inhibitory Effect of Copper Nanoparticles Synthesized by Lactobacillus sp. on Pathogenic Bacterial Strains - Hamood, Ihab Ahmad; Hamad, Shefaa Abas; Salman, Warqaa Latef (Universitas Muhammadiyah Sidoarjo, 2025)
Lactobacillus sp. against the pathogenic bacteria Staphylococcus aureus and Pseudomonas aeruginosa. The nanoparticles were produced using the bacterial cell-free filtrate, and their physicochemical properties were analyzed using several characterization techniques, including X-ray diffraction (XRD), UV–Visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), energy-dispersive X-ray spectroscopy (EDX), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The results confirmed the successful synthesis of pure, spherical CuNPs with particle sizes ranging from 40 to 110 nm. The antibacterial potential of the synthesized nanoparticles was assessed using the well diffusion method at five concentrations: 1000, 500, 250, 125, and 62.5 µg/mL. The concentrations of 1000 µg/mL and 500 µg/mL demonstrated notable antibacterial effects, with inhibition zones averaging 12 mm and 10 mm against Staphylococcus aureus, and 10 mm and 8 mm against Pseudomonas aeruginosa, respectively. Highlights: CuNPs were successfully synthesized using Lactobacillus sp. in an eco-friendly method. Particles were spherical, 40–110 nm in size, confirmed by various techniques. Higher concentrations effectively inhibited S. aureus and P. aeruginosa. Keywords: Copper Nanoparticles, Lactobacillus sp., Antibacterial, Staphylococcus aureus, Pseudomonas aeruginosa